1996
DOI: 10.1021/np960521t
|View full text |Cite
|
Sign up to set email alerts
|

Fusaricide, a New Cytotoxic N-Hydroxypyridone from Fusarium sp.

Abstract: A new cytotoxic N-hydroxypyridone, fusaricide (1), was isolated from a Fusarium sp. Its structure was solved by X-ray diffraction and spectroscopic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…18 Furthermore, many of these alkaloids exhibit cancer cell growth-inhibitory activity and are investigated as potential anticancer agents. Examples include cytotoxic fusaricide (1) 19 and melicobisquinolinone B (2, Figure 1). 20 In addition, zanthosimuline (3) is active against multidrug resistant KB-VI cancer cells, while huajiaosimuline (4) exhibits a selective cytotoxicity profile showing the greatest activity with estrogen receptor-positive ZR-75-1 breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, many of these alkaloids exhibit cancer cell growth-inhibitory activity and are investigated as potential anticancer agents. Examples include cytotoxic fusaricide (1) 19 and melicobisquinolinone B (2, Figure 1). 20 In addition, zanthosimuline (3) is active against multidrug resistant KB-VI cancer cells, while huajiaosimuline (4) exhibits a selective cytotoxicity profile showing the greatest activity with estrogen receptor-positive ZR-75-1 breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H- 1 H COSY spectrum of 1 indicated three spin systems: C5–C6, C7–C8(-C18)–C9–C10(-C17)–C11, and C13–C15, which were also verified by the corresponding HMBC correlations ( Figure 3 ). Meanwhile, the HMBC correlations from the methyl group CH 3 -16 to C-7, C-11, C-12 and C-13, and from H-7 to C-2 (δ C 159.4), C-3 (δ C 114.6), and C-4 (δ C 165.8), as well as a correlation from H-13 to the oxygenated olefinic carbon C-4, suggested that compound 1 should be an analog of fusaricide [ 25 , 26 ]. However, one oxygenated methine (instead of a methylene) at 11-position and one methoxy group at 1-position were observed in 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configuration of compound 1 was determined by comparing its optical rotation with those of ( 3 ) [ 28 ], cordypyridone C ( 6 ) [ 27 ], 14-hydroxycordypyridone C ( 7 ) [ 27 ] and fusaricide ( 8 ) [ 25 , 26 , 27 ], and its CD with that of compound 3 . The absolute configuration of the p -bromobenzoate of compound 7 was established using anomalous scattering X-ray crystallographic methods [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was pre‐established that proinflammatory cytokines like TNF‐α and interleukin‐6 (IL‐6) become attractive targets for adjuvant treatment of cancer as they are master regulators of tumor‐related inflammation and tumorigenesis (Grivennikov & Karin, ). As per showed in Figure , alkaloids with pyrano[3,2‐c]pyridone and pyrano[3,2‐c]quinolone like fusaricide (1, Figure ) (McBrien et al., ), melicobisquinolinone‐B (2, Figure ) (Kamperdick, Van, Van Sung, & Adam, ), zanthosimuline (3, Figure ), and huajiaosimuline (4, Figure ) (Chen et al., ) referred as potential anticancer agents. Additionally, Quinolactin‐A (Sasaki et al., ) (5, Figure )—a 4‐quinolone alkaloid, isolated from the cultured broth of Penicillium sp.…”
Section: Introductionmentioning
confidence: 99%